Kinds of weed control in sunflower culture through different hoeings - Fleck, Nilson Gilberto; da Silva, Paulo Regis Ferreira (Pesquisa Agropecuaria Brasileira, 1991)
A field experiment was carried out in the region of the central depression of Rio Grande do Sul, in Brazil, with the objective of establishing levels of weed interference in sunflower cultures, and evaluating physical methods that favor weed control efficiency with less crop damage. One or two hoeings were tested, manually or mechanically, in the whole area, between rows, or only in sunflower rows, besides a control treatment with no hoeing. The results show the necessity of weed control for the obtention of a sunflower improved grain yield. For this purpose one operation in the whole area is sufficient. Weed removal from between crop rows was the measure that showed the best control. However, this operation only in sunflower rows is insufficient for controlling weeds. Manual or mechanical hoeings were equivalent in terms of sunflower yield.